(untitled) (Nepalese Medical Journal, 2018)
Intravenous fluids are a core element in the resuscitation of critically ill patients, and choice & management strategies vary widely in day-to-day medical practice. With the advancement in the understanding and implementation of aggressive fluid resuscitation, has also come a greater awareness of the resultant fluid toxicity. As such, the discussion regarding intravenous solutions continues to evolve especially as it pertains to their effect on kidney and metabolic function, electrolytes, and ultimately patient outcome. This review discusses the fluid management from the perspective of resuscitative strategies, and is expected to guide clinical practitioners in fluid decision-making for common clinical scenarios encountered at acute care setups.